2018
DOI: 10.22437/pena.v7i2.5289
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Mahasiswa Tentang Pendidikan Karakter Pada Buku Teks Reading Di Perguruan Tinggi Swasta

Abstract: Abstrak Tujuan penelitian ini adalah untuk menganalisa eksistensi dari nilai pendidikan karakter pada buku teks yang digunakan pada mata kuliah Reading di STKIP PGRI Sumatera Barat. Penelitian ini adalah penelitian kualitatif dimana data pada penelitian ini dikumpulkan dengan wawancara. Subjek pada penelitian ini adalah dosen yang telah dan mengajar pada mata kuliah Reading dan mahasiswa yang telah mengikuti mata kuliah tersebut. Objek dari penelitian ini adalah buku teks yang digunakan pada mata kuliah … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
2
0
4
Order By: Relevance
“…Cheng [60] likewise confirmed that cognitive engagement, as a mediator, will influence the effect of self-efficacy and learning motivation on academic achievement in the hospitality curriculum. Motivation encourages students to think and improve when facing challenges and tasks [59]. Previous research focused mostly on the effect of cognitive engagement on academic performance.…”
Section: Moderating Effect Of Cognitive Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng [60] likewise confirmed that cognitive engagement, as a mediator, will influence the effect of self-efficacy and learning motivation on academic achievement in the hospitality curriculum. Motivation encourages students to think and improve when facing challenges and tasks [59]. Previous research focused mostly on the effect of cognitive engagement on academic performance.…”
Section: Moderating Effect Of Cognitive Engagementmentioning
confidence: 99%
“…Therefore, our study also plans to discover the mediating role of self-regulated learning in the relationship between DLA and career self-efficacy. According to Corno and Mandinach [58] and Sesmiyanti et al [59], cognitive engagement indicates students' degree of commitment to tasks or challenges and is a type of motivation encouraging students to improve. Therefore, our study also plans to explore whether cognitive engagement is a critical moderator in the relationship between the three other variables.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini mengakibatkan materi yang diberikan kurang variatif dan menjemukan sehingga mengakibatkan mahasiswa tidak tertarik untuk membaca materi tersebut. Hal ini sejalan dengan penelitian yang dilakukan oleh Sesmiyanti et al (2018) yang menemukan bahwa minat membaca mahasiswa prodi Pendidikan Bahasa Inggris masih kurang.…”
Section: Pendahuluanunclassified
“…Materi ajar atau bahan ajar dirancang, disusun, dan dikembangkan untuk membantu baik peserta didik maupun pendidik dalam proses pembelajaran agar dapat membangun suasana pembelajaran yang lebih hidup, menarik, dan inovatif (Sesmiyanti et al, 2018). Bahan ajar ini berperan sebagai pencerminan sudut pandang yang tajam dan inovatif mengenai pengajaran serta aplikasinya, penyajian sumber pokok masalah yang tersusun rapi dan bertahap sesuai dengan kebutuhan dan minat peserta didik yang disajikan dengan metode -metode yang dapat memotivasi peserta didik, dan penunjang bagi latihan dan tugas praktis sebagai bahan evaluasi yang tepat guna (Iskandarwassid dan Sunendar dalam Bahtiar, 2015).…”
Section: Pendahuluanunclassified
“…Character education refers to teaching or giving values to the students. Sesmiyanti et al (2018) define "Pendidikan karakter merupakan sebuah pengembangan kemampuan yang berkelanjutan dan dinamis dalam diri manusia dalam memahami nilai-nilai positif, aktif dan stabil dalam diri individu".…”
Section: Nowadays Stkip Pgri Sumatera Barat Especially In English Studyunclassified